Upaya Pemulihan Mental Anak Korban Child Abuse Melalui Play Therapy - Fadhilah, Aulia Nisa; Ulin Nihayah; Karim, Abdul (Universitas Muhammadiyah Malang, 2025)
This research highlights the issue of child protection as a gift and responsibility that should be implemented by parents and society, in accordance with the provisions of the Child Protection Law No. 23 of 2002. Although children have rights that must be safeguarded, there is often a gap between ideal concepts and the harsh reality. Acts of violence against children, whether physical, emotional, sexual, or neglect, pose serious problems, especially when the perpetrators come from environments that should provide protection. The negative impacts of child abuse include trauma, low self-esteem, psychological disorders, and a decline in performance, significantly affecting the future of children. Law Number 11 of 2012 emphasizes the need for a rehabilitative approach rather than punishment for children in conflict with the law. This research employs field observation methods focusing on the implementation of social programs for children who are victims of child abuse. The activities involve socialization, empowerment of children's interests and talents, play, and sharing experiences. The results show positive psychological changes in children, reflected in increased enthusiasm and awareness of their right to education. Therefore, collaboration among parents, society, and the government is crucial in protecting children. Adequate legal protection and a rehabilitative approach are key to ensuring that children can grow and develop optimally in line with their human rights.